Pengaruh Rasio Profitabilitas dan Rasio Solvabilitas Terhadap Return Saham - Linda, Linda; Ramli, Rosmini (Universitas Muhammadiyah Metro, 2024)
This research aims to determine the effect of profitability ratios as measured by Return On Assets (ROA), Return On Equity (ROE), Earning Per Share (EPS), and solvency ratios as measured by Debt to Equity Ratio (DER) on stock returns in sub banking sector listed on the Indonesia Stock Exchange (BEI) during the 2018-2022 period. This research method uses quantitative methods with descriptive and associative approaches. The population in this research was 47 banks and the sample used in this research was 18 banks, the sample was selected based on purposive sampling. The data analysis technique used in this research is panel data regression analysis using eviews 12 software. The results of the study show that Return On Assets (ROA) and Earning Per share (EPS) have a positive effect on stock returns, Return On Equity (ROE) has a positive effect on stock returns. negative on stock returns, while the Debt to Equity Ratio (DER) has no effect on stock returns